Three Interpretations of the Truth of a Work of Art – Gadamer, Heidegger, Šliogeris - Daknys, Mantas (Problemos, 2023)
This article examines interpretations of ontological truth of the work of art in the philosophies of Arvydas Šliogeris, Hans G. Gadamer and Martin Heidegger. All of them believe that artwork may reveal the ontological truth. This common feature suggests the possibility to consider these three interpretations as a Heideggerian-type understanding of art. This paper argues that, while sharing the belief about the possibility of ontological truth in the artwork, their concepts of truth are fundamentally different, precisely because of the relation with language. In the first part of the article, the ontologies of works of art, the structures of experience, the importance of language and the interpretations of truth by the three philosophers are discussed. The second part explicates the essential points of tension and similarities between their concepts of ontology and the truth of artwork. The research reveals that language, as the basic plane of the junction with the world, in the experience of a work of art is more misleading than truth-revealing.